Mr. Putter & Tabby : Drop the ball - Rylant, Cynthia; Howard, Arthur (Boston : Houghton Mifflin Harcourt, 2013)
Mr. Putter and his cat Tabby take time off from napping to play on the Yankee Doodle Dandies baseball team.
Horn Book
Kirkus Review
School Library Journal
Horn Book, April 2014
Kirkus Review, August 2013
School Library Journal, July 2013
Keywords: Baseball -- Juvenile fiction; Cats -- Juvenile fiction; Old age -- Juvenile fiction; Baseball -- Fiction; Cats -- Fiction; Old age -- Fiction; Baseball -- Fiction; Cats -- Fiction; Old age -- Fiction; Readers (Publication)